After portal branch ligation in the rat, cellular proliferation in associated with selective induction of c-Ha-ras, p53, cyclin E, and Cdk2. Issue 1 (1st July 2001) - Stärkel, P; Lambotte, L; Sempoux, C; De Saeger, C; Saliez, A; Maiter, D; Horsmans, Y
Abstract : BACKGROUND: In liver regeneration after portal branch ligation we previously showed that early cellular changes are observed in both the proliferating and atrophying liver lobes. They are therefore not indicative of future proliferative response. In this study we attempted to define precisely, in the same model, the time at which the cellular processes diverge between the lobes by measuring various parameters associated with cellular proliferation. We also investigated the possible role of inhibitors of cell proliferation in the absence of progression towards the S phase in the atrophying lobes. AIMS: Expression of p53, c-Ha-ras, cyclin E, cyclin dependent kinase (Cdk2), transforming growth factor (TGF)-β, and interleukin (IL)-1α and IL-1β were assessed in relation to their potential role in proliferating and atrophying cellular phenomenons. METHODS: Immunohistochemistry, northern blotting, western blotting, and reverse transcription-polymerase chain reaction were performed, mainly at time points corresponding to mid-G1/S phase progression (8–24 hours after surgery). RESULTS: The common and thus most likely non-specific response was still evident 5–8 hours after surgery and included an increase in IL-1 mRNA as well as p53 and cyclin E proteins. From 12 hours onwards, p53, c-Ha-ras, cyclin E, and Cdk2 were selectively induced in proliferating lobes whereas IL-1β was predominantly activated in atrophying lobes. No changes in TGF-β or IL-1α expression were observed at the same time points in any of the liver lobes. CONCLUSIONS: The initial response to portal branch ligation and thus probably to partial hepatectomy seems to be non-specific for at least eight hours. Thereafter, p53, c-Ha-ras, cyclin E, and Cdk2 seem to drive cellular proliferation while IL-1β is associated with cellular atrophy. In contrast, TGF-β and IL-1α do not seem to play a role in determining the commitment of cells towards atrophy or proliferation.